2020
DOI: 10.1021/acs.orglett.0c02735
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Polysubstituted Pyrroles via Silver-Catalyzed Oxidative Radical Addition of Cyclopropanols to Imines

Abstract: A silver-catalyzed formal [3 + 2] cycloaddition reaction, with cyclopropanols as a C3 subunit and imines as a two-atom subunit, is developed. The reaction takes place under mild conditions and produces a broad array of polysubstituted pyrroles in medium to high yields. It represents the first example of oxidative radical addition to imines, thus offering a new choice for the direct C–H functionalization of imines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…In 2020, a radical [3 + 2] cycloaddition reaction between cyclopropanols and imines for the preparation of polysubstituted pyrroles was reported by Zho et al [65] Among examining various silver salts, including AgNO 3 , AgOAc, Ag 2 CO 3 , AgBF 4 , and AgO 2 CCF 3 , control experiments showed that AgO 2 CCF 3 in the presence of Na 2 S 2 O 8 is the better catalyst for the cycloaddition reaction. Synthesis of N-aryl-pyrazoles through ringopening of cyclopropanols was developed by two research groups.…”
Section: Ring-opening Cyclization Reaction Of Cyclopropanolsmentioning
confidence: 99%
“…In 2020, a radical [3 + 2] cycloaddition reaction between cyclopropanols and imines for the preparation of polysubstituted pyrroles was reported by Zho et al [65] Among examining various silver salts, including AgNO 3 , AgOAc, Ag 2 CO 3 , AgBF 4 , and AgO 2 CCF 3 , control experiments showed that AgO 2 CCF 3 in the presence of Na 2 S 2 O 8 is the better catalyst for the cycloaddition reaction. Synthesis of N-aryl-pyrazoles through ringopening of cyclopropanols was developed by two research groups.…”
Section: Ring-opening Cyclization Reaction Of Cyclopropanolsmentioning
confidence: 99%
“…The latter process is challenging due to the relatively strong OÀ H bond (typical BDE values 103-105 kcal mol À 1 ). [4] The traditional methods for the generation of radicals A with the subsequent addition to double bonds of olefins require strong oxidative conditions provided by stoichiometric oxidants [5] and/or transition metal derivatives (Ag(I), [6][7][8] Fe(III), [9][10][11] Mn(III) [12][13][14] ) and elevated temperatures. [5,6,10,11,14] Currently, photoredox catalysis offers a number of bypassing strategies that allow the generation of ketoalkyl radicals from cyclopropanols [15,16] and even unstrained cycloalkanols under mild conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Xiong et al developed an efficient protocol for the synthesis of polysubstituted pyrroles via ketenimine formation/Ag(I)‐catalyzed alkyne cycloisomerization [18]. In 2020, Zhu described direct synthesis of polysubstituted pyrroles via an Ag‐catalyzed formal [3 + 2] cycloaddition reaction [19]. Recently, De Sarkar et al reported an efficient electrochemical method for the synthesis of polysubstituted pyrroles [20].…”
Section: Introductionmentioning
confidence: 99%